Treatment of bisphosphonate-related osteonecrosis of the jaws – a report of seven cases - Jakiel, Joanna; Rahnama, Mansur; Szczerba-Gwóźdź, Joanna (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : The aim of the study was to report on seven cases of BRONJ treated with surgical debridement, oral antibiotics and gentamicin-collagen sponge (Collatamp EG) placed in the bone wound. Material and methods : Seven patients with 9 sites of BRONJ stage 2 were included in the study. Perioperative oral antibiotics, surgical debridement and/or sequestrotomy and gentamicin-collagen sponge (Collatamp EG) were used. Postoperative monitoring was carried out for the next 3 months. Results : Three weeks after the surgery, six sites of BRONJ in five patients were treated successfully. In two patients on three sites BRONJ stage 1 was observed. Three months after surgery another two sites healed fully. In one patient there was still BRONJ stage 1, however, the area of exposed bone was visibly reduced. Conclusions : The use of surgical debridement together with oral antibiotic therapy and collagen-gentamycin sponge indicates positive results regarding the surgical treatment of BRONJ.